Advances in Management of Bladder Cancer—The Role of Photodynamic Therapy - Kubrak, Tomasz; Karakuła, Michał; Czop, Marcin; Kawczyk-Krupka, Aleksandra; Aebisher, David (Molecules (Basel, Switzerland), 2022)
Photodynamic therapy (PDT) is a non-invasive and modern form of therapy. It is used in the treatment of non-oncological diseases and more and more often in the treatment of various types of neoplasms in various locations including bladder cancer. The PDT method consists of local or systemic application of a photosensitizer, i.e., a photosensitive compound that accumulates in pathological tissue. Light of appropriate wavelength is absorbed by the photosensitizer molecules, which in turn transfers energy to oxygen or initiates radical processes that leads to selective destruction of diseased cells. The technique enables the selective destruction of malignant cells, as the photocytotoxicity reactions induced by the photosensitizer take place strictly within the pathological tissue. PDT is known to be well tolerated in a clinical setting in patients. In cited papers herein no new safety issues were identified. The development of anti-cancer PDT therapies has greatly accelerated over the last decade. There was no evidence of increased or cumulative toxic effects with each PDT treatment. Many modifications have been made to enhance the effects. Clinically, bladder cancer remains one of the deadliest urological diseases of the urinary system. The subject of this review is the anti-cancer use of PDT, its benefits and possible modifications that may lead to more effective treatments for bladder cancer. Bladder cancer, if localized, would seem to be a good candidate for PDT therapy since this does not involve the toxicity of systemic chemotherapy and can spare normal tissues from damage if properly carried out. It is clear that PDT deserves more investment in clinical research, especially for plant-based photosensitizers. Natural PS isolated from plants and other biological sources can be considered a green approach to PDT in cancer therapy. Currently, PDT is widely used in the treatment of skin cancer, but numerous studies show the advantages of related therapeutic strategies that can help eliminate various types of cancer, including bladder cancer. PDT for bladder cancer in which photosensitizer is locally activated and generates cytotoxic reactive oxygen species and causing cell death, is a modern treatment. Moreover, PDT is an innovative technique in oncologic urology.